Effects of weld size on stress concentration factors of CHS-CFSHS joints - Delei Yang; Lewei Tong (Fracture and Structural Integrity)
This paper aims to disclose the effects of weld size on hot spot stress in the calculation of fatigue performance of the joints. For this purpose, the author explored the hot spot stress of CHS-CFSHS T-joints, which consists of circular hollow section (CHS) braces and concrete-filled square hollow section (CFSHS) chords. After reviewing the previous studies and the relevant specifications on weld size, the author probes into the effects of weld size on the stress concentration factor (SCF) of CHS-CFSHS joints via finite-element analysis. The analysis show that the weld size directly affected the hot spot stress in both conditions, and the influence laws were largely the same; with the increase of weld size, the brace-side SCF plunged when the chord-size weld size remained the same, but the chord-side SCF changed slightly when the brace-side weld size was constant; the brace-side and chord-side SCF declined when the brace-side and chord-side weld sizes increased by the same amount. This research successfully determined the weld sizes that are consistent with the relevant specifications, and safe and simple to apply in actual engineering.